Portfolio-Based Assessment Practices of Selected High School English Language Teachers in Metro Manila - Medrano, Sherry Ann C. (International Journal of Psychosocial Rehabilitation, 2020)
Portfolio-based assessment is a tool used to keep track of student’s progress in the classroom over time. Moreover, it does not only individualize student’s learning, but also help teachers improve their instruction. This study sought to identify the portfolio assessment practices of selected high school language teachers in Metro Manila. It employedboth quantitative and qualitative research designs. The descriptive method of research was used in the study, employing both quantitative and qualitative research designs. A total of 20 junior high school English teachers participated in the study. First, a survey was conductedto determinethe profile of the respondents. Then, an interviewwas doneto gather the necessary data regarding the teachers’ use of portfolio assessment.Overall, the teachers foundportfolio as an important assessment tool inmonitoringstudent’s progress and in keeping record of what they have accomplished in class.Furthermore, the teacher-respondents identified the use ofportfolioas a practical assessment tool, since it provides completeand concrete learning evidence. Portfoliobased assessment has been also found useful in visualizing the strengths and weaknesses of the students in the K to 12 Classroom.However, the study revealed that portfolio assessment is often done informally and is less effective to the students in lower sections. Thus, the findings suggest that teachers must practice using formalportfolio-based assessment with distinct pattern or criteria to enhance the reliability of the portfolio, since teaching in the K to 12 classrooms is student-centered and outcome-based.